BS EN ISO 4982. Plastics piping systems for non-pressure underground conveyance and storage of non-potable water. Arch-shaped, corrugated wall chambers made of PE or PP used for retention, detention, transportation and storage systems. Product specifications and performance criteria. (3rd May 2022) - British Standards Institution,
No abstract available